The effect of sanctions and tax penalties in the taxpayer's obligation - Shakir Baghdadi, Ali Ghanim; Haider Omran Seher, Arshed Makki Rashid, (Opción, 2019)
The paper draws critical review of the existing research literature to concepts of taxations and its related dynamics, which can affect the overall effectiveness of the tax obligations and tax payment system of Iraq via comparative qualitative research methods. As a result, the danger of discipline has urged citizens to be progressively disposed towards the duty evasion disposition. In conclusion, the risk of discipline is less inclined to be compelling in deflecting individuals who as of now have solid goals to agree to charge laws yet bound to build their negative aims to consent.